2021
DOI: 10.1002/admi.202001988
|View full text |Cite
|
Sign up to set email alerts
|

MoS2/Paper Decorated with Metal Nanoparticles (Au, Pt, and Pd) Based Plasmonic‐Enhanced Broadband (Visible‐NIR) Flexible Photodetectors

Abstract: development of flexible electronics, especially in the biomedical field, which has led to an exploration of flexible substrate photodetectors. [7,8] These devices are far more compact and cost-effective compared to the conventional bulk substrate devices and reduce the expenditure on material as well as fabrication. [9] Still, several issues need to be addressed. [10] Some of the issues are surface roughness, thermal stability, and cleanroom compatibility. Almost all of the flexible substrates utilized (polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 59 publications
0
41
0
Order By: Relevance
“…On the other hand, Guo et al prepared Au NSs on MoS 2 surface using magnetron sputtering that showed a responsivity of only 64 mA/W over the 700–1600 nm wavelength region . Very recently, Selamneni et al used solution of various metal NPs (Au, Pt, and Pd) to coat the MoS 2 surface and demonstrated flexible photodetectors with a peak responsivity of 99.3 and 46.03 mA/W under visible and NIR regions . The low responsivities of the reported studies are ascribed to the inefficient transfer of electrons from metal to semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Guo et al prepared Au NSs on MoS 2 surface using magnetron sputtering that showed a responsivity of only 64 mA/W over the 700–1600 nm wavelength region . Very recently, Selamneni et al used solution of various metal NPs (Au, Pt, and Pd) to coat the MoS 2 surface and demonstrated flexible photodetectors with a peak responsivity of 99.3 and 46.03 mA/W under visible and NIR regions . The low responsivities of the reported studies are ascribed to the inefficient transfer of electrons from metal to semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…The rise time was found to be 17.8 ms and the decay time was found to be 16.8 ms. A comparison of the figures of merit for our photodetectors and literature reported photodetectors are provided in the supporting information ( Table S1 ). The devices demonstrated here perform superior to reported MoS 2 based photodetectors with Au nanoparticles in terms of responsivity and response time ( Guo et al., 2019 ; Lin et al., 2020 ; McManus et al., 2018 ; Rahmati et al., 2019 ; Selamneni et al., 2021 ). Comparisons with reports on solution-processed transition metal dichalcogenide-based photodetectors have also been made ( Abid et al., 2019 ; Alzakia et al., 2020a , 2020b ; Kim et al., 2021 ; Li et al., 2020a ; Liu et al., 2019 ; McManus et al., 2017 ; Pulikodan et al., 2020 ; Seo et al., 2019 ).…”
Section: Resultsmentioning
confidence: 63%
“…The XRD pattern of synthesized SnS is well-matched with JCPDS No. 39-0354, indicating an orthorhombic structure. , Further, two more peaks located at 22 and 16° are attributed to the paper substrate . XPS results were used to validate the chemical composition of the SnS.…”
Section: Resultsmentioning
confidence: 99%